A New Approach for the Patient with Erectile Dysfunction - Ian Eardley; Hartmut Porst; Ignacio Moncada; Béatrice Cuzin; Ian Eardley (European Medical Journal Urology, 2015)
This satellite symposium was held in two sessions. The first session was offered in a traditional format where invited experts reviewed and discussed the latest concepts and developments on the management of erectile dysfunction (ED). During the second session, experts discussed clinical cases from their real-life practice in an interactive format, to facilitate discussions with the audience, and to provide participants with the most relevant aspects of ED. The symposium objectives were to review and discuss the current status of the management of ED and treatment needs for patients with ED, and to explore the latest evidence on the use of topical alprostadil cream (Vitaros®, Virirec®, Vytaros®)1 – who benefits the most?